A Comprehensive Review on Teaching Students with Learning Disabilities: The Potential of VR and AR Technology - Rushali Verma; Sangeeta Kakkar; Ashu Kumari (International Journal of Children, 2024)
In terms of enhancing learning experiences, the use of virtual reality (VR) and augmented reality (AR) in education has shown encouraging outcomes. These technologies offer immersive, interactive environments that are extremely beneficial to students who struggle with learning. to assess how VR and AR affect learning outcomes in general as well as motivation, engagement, and academic performance. We'll examine how these resources might be applied to support children who face learning challenges. It also looks to determine the difficulties and possibilities these technologies may provide in special education in the future. A comprehensive search of the literature was carried out utilizing a range of sources, including PubMed, Google Scholar, and specialized academic databases. It was found that a great deal of potential is needed for VR/AR technology to transform special education. They provide students with learning challenges and individualized flexible learning experiences that improve their motivation, engagement, and academic achievement. Although VR/AR can be useful tools for improving the educational experiences of children with learning impairments, more study and funding are required to remove current obstacles and reach VR and AR’s full potential in children with special needs. Students may study and engage with complicated subjects in a safe, supervised environment by using VR and AR, in particular, to construct simulations and scenarios that are not possible in conventional classroom settings. With the ability to create personalized learning pathways that suit various learning styles and speeds, these technologies can also be customized to match the particular needs of each student. Also, the excitement and engagement that VR and AR provide can encourage a deeper interest in learning, which is essential for long-term academic achievement.
Keywords: Learning disabilities; Personalized learning; Virtual reality (VR); augmented reality (AR); special education